Two wavelength-shifting molecular beacons for simultaneous and selective imaging of vesicular miRNA-21 and miRNA-31 in living cancer cells - Bohländer, Peggy; Abba, Mohammed L.; Allgayer, Heike (Organic & biomolecular chemistry, 2016)
Two molecular beacons were designed as complementary fluorescent imaging probes for miRNA-21 and miRNA-31. Both beacons were prepared by a combination of solid-phase protocol and Cu(I)-catalyzed cycloaddition chemistry. The four photostable and bright fluorophores were attached to 2′-positions in the stem part of the two beacons. One beacon was labeled by a green-to-red emitting and the other by a blue-to-yellow emitting energy transfer pair. This two by two combination yields the four color emission readout. In vitro experiments demonstrate rapid and highly selective opening of both molecular beacons upon addition of the complementary target RNA and excellent green : red and blue : yellow emission color contrasts. Confocal microscopy of selected cancer cell lines provides evidence that a four color imaging of versicular miRNA-21 and miRNA-31 can be achieved both selectively and simultaneously upon transfection by the beacons, and that the fluorescent readouts track well with miRNA levels determined by PCR.